2014
DOI: 10.1111/bij.12339
|View full text |Cite
|
Sign up to set email alerts
|

Female polyandry and size-assortative mating in isolated local populations of the Japanese common toadBufo japonicus

Abstract: In anurans, female polyandry under male harassment is distributed across taxa because of external aquatic fertilization. According to the sexual selection theory, male–male competition for access to females is affected by the operational sex ratio (OSR) and population density. The Japanese common toad, Bufo japonicus, is widespread in mainland Japan, and like the European common toad, B. bufo, it engages in explosive breeding. In this study, we observed the breeding behaviour of B. japonicus in isolated local … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 24 publications
0
6
0
Order By: Relevance
“…Sztatecsny et al 2006) or from the presence of free swimming sperm from multiple males (e.g. Hase and Shimada 2014). However, we found relatively low PA, with some populations exhibiting little or no evidence of polyandry (Fig.…”
Section: Discussionmentioning
confidence: 59%
“…Sztatecsny et al 2006) or from the presence of free swimming sperm from multiple males (e.g. Hase and Shimada 2014). However, we found relatively low PA, with some populations exhibiting little or no evidence of polyandry (Fig.…”
Section: Discussionmentioning
confidence: 59%
“…In the case of mate choice in the toads, in particular miyakonis , species recognition seems not to be significant due to geographically isolation. In addition, male-male competition is a central factor rather than female preference in the reproductive behavior of B. japonicus (Hase & Shimada 2014). An exploration of the ecological function of the species recognition abilities we detected lies beyond the scope of this study.…”
Section: Discussionmentioning
confidence: 99%
“…Most empirical studies have found a large male advantage (Chajma & Vojar, 2016;Rausch et al, 2014). Alternatively, a size-assortative (Cogălniceanu et al, 2013;Hase & Shimada, 2014;Lu et al, 2009) or random mating pattern with respect to size of mating partners has also been described (Elmberg, 1987;Sullivan, 1989).…”
Section: Explosive Breeding and Non-assortative Matingmentioning
confidence: 99%
“…On the other hand, an optimal ratio between the size of partners forming an amplexus can determine an increase in the percentage of fertilised eggs through a favourable juxtaposition of partners as well as resistance to displacement from competing males, so that it is advantageous for smaller individuals to choose smaller partners, resulting in a size selection of mates that are not necessarily the larger ones (Bastos & Haddad, ; Pfennig, ). As a result of the mentioned selective pressures, assortative mating based on body size is in many cases favoured (Chajma & Vojar, ; Hase & Shimada, ).…”
Section: Introductionmentioning
confidence: 99%